Government-Assisted Rental Accommodations: Should They Accommodate Homeowners with Unmet Needs? - Golant, Stephen (Maine Policy Review, 2003)
Stephen Golant, a national expert on elderly housing concerns, describes the types and seriousness of housing problems facing elders nationally and in Maine. Although older adults are predominantly homeowners, national policymakers often downplay the needs of this group and hand over responsibility to state and local governments. The author reviews arguments that cynics have offered for deemphasizing older homeowners’ needs, and discusses various solutions to meet those needs. He poses the question: Do we unrealistically romanticize aging in place? As the title of the article suggests, Golant proposes that a good solution to the needs of older homeowners is to increase the availability of government-assisted rental accommodations, ideally accompanied by supportive services.
Keywords: government housing assistance; affordable housing; aging in place